VARIABILITE DES CARACTERES TARSE, AILE PLIEE ET L’EVOLUTION PONDERALE CHEZ DEUX LIGNEES DIVERGENTES DE LA PERDRIX GAMBRA (Alectoris barbara, BONNATERRE, 1792) - MEZERDI, FARID; HUGUENIN, JOHANN; BELHAMRA, MOHAMED (Courrier du Savoir; Vol. 19 (2015): COURRIER DU SAVOIR(Mars), 2015)
ABSTRACT Our study was focused on the monitoring of the divergent growth rate characters Weight, Tarsus and folded Wing, in two strains Fast Slow gambra partridge, breaded and controlled in the Hunting Center of Zéralda. For three generations, during 13 weeks, we conducted 8.946 measures a total sample of N = 213 birds. Individual data, in both strains were determined by growth curves adjustments estimated using the Gompertz model. The average values hatching weights characters, the wing folded and the tarsus are in favor of the FL line. We confirmed this prediction by analysis of variance "ANOVA test" for body mass, tarsus length and wing that are significantly higher in the FL line from the line SL. We have demonstrated that the secondary sexual character "pin" developing for the duration of the experiment becomes significantly apparent from the 140 days of age (20 weeks).Our results demonstrate the effectiveness of the selection scheme, the two divergent lines significantly. Genetic factors are significantly responsible for the fast growth or not. We can move forward, that the requirements of the physical, physiological and behavioral unique to this group of birds have been optimized. KEYWORDS: Barbary Partridge (Alectoris barbara), fast line LR, slow line Ll, captive population, Restocking.